Assessment of adverse events following first dose of COVISHIELD in healthcare workers of a tertiary care hospital in western Uttar Pradesh: A prospective observational study - Shivangna Singh; Suchi Jain; Bushra Hasan Khan; Gautam, Vivek; Mayank Batola (Asian Journal of Medical Sciences, 2022)
Background: COVID‑19 pandemic is a great health challenge around the world. Immunization appears best preventive strategy where monitoring the safety of COVID-19 vaccines is immensely important as limited safety data available on them. Aims and Objectives: This study was conducted to perform safety surveillance and causality assessment of adverse events following immunization (AEFI) with COVID-19 vaccine. Materials and Methods: This prospective observational study was conducted on healthcare workers who received their first dose of COVISHIELD during first phase of COVID-19 vaccination in January–February 2021 at F.H. Medical College and Hospital, Tundla, Firozabad. Approval for the study was taken from institutional ethical committee. The details of AEFIs were collected and duly noted in standard AEFI case reporting form of Ministry Of Health And Family Welfare, Immunization Division, Govt. of India and reported to District Immunization Officer. Causality assessment was done in accordance with protocol of the World Health Organization. Results: Out of 419 vaccinees, 210 had developed AEFIs, and 527 AEFIs were reported considering the fact that one recipient could have experienced multiple AEFIs. Majority AEFIs were related to general disorders and administration site conditions (67.35%), where fever (28.46%), chills (16.69%),and pain at injection site (15.75%) were more common, followed by musculoskeletal and connective tissue disorders (19.55%) where myalgia (18.03%) was more commonly reported. Out of 527 AEFIs reported, majority (524, 99.43%) showed consistent causal association to immunization and 3 (0.57%) AEFIs showed inconsistent association. AEFIs classified as consistent causal association (524) mostly were vaccine product related reactions (520, 99.23%) and rest (4, 0.76%) were immunization anxiety related reactions. Severity assessment of AEFIs was done using Modified Hartwig and Siegel Severity Scale, out of total 527 AEFIs reported 60.9% were of mild severity and rest 39.1% were categorized as moderate severity. Conclusion: As adverse events post-vaccination with COVISHIELD were mild to moderate in severity and lasted for a short duration, the inconvenience caused by these AEFIs outweigh the protection offered by the vaccination against COVID-19.